The pattern of buddhist teachers strategies management for religious behavior conflicts in Lombok - I Ketut Damana (Institute of Computer Science (IOCS), 2022)
The Buddhist teacher's goal of conflict is of course required to use a psychological approach. The less than ideal conditions of the teacher's purposeful behavior in the managed lesson process are not opposite. The importance of the strategy of religious teachers tends to be seen in the character education of the attendees. Descriptive qualitative research method is used on this research. The research instruments were interviews, observations, documentation, and respondents with several related devices. In reality, not all Buddhist teachers deliver material with curriculum. This has an impact on improving the continuity of education, i.e. there are students who are not taught Buddhism. Data analysis is using Iceberg model. The results of the study can be concluded as; the innovation process occurs from the conflict of teacher behavior, the implementation of the innovation pattern of the teacher's strategy, the structure of the advantages and disadvantages of teacher management and the mental model of teacher behavior.